Chemical design of high performance SPR biosensor based on a dielectric nanoparticle assembly supported onto a gold thin film. Issue 5 (26th August 2022) - Berling, Pier; Dolci, Mathias; Zafeiratos, Spyridon; Gehin, Thomas; Leuvrey, Cédric; Kiefer, Céline; Wagner, Déborah; Boulmedais, Fouzia; Pichon, Benoit P.
Abstract : The SPR system is a very efficient tool to investigate original and highly efficient biosensors and to study molecular recognition mechanisms. Abstract : The SPR system is a very efficient tool to investigate original and highly efficient biosensors and to study molecular recognition mechanisms. We report on the design of an original nano-architecture which consists of iron oxide nanoparticle assemblies supported on gold thin films and which acts as a very efficient SPR sensor. The build-up of the sensor consists of a three-step CuAAC "click" reaction process which allows the selective and easy preparation of a robust platform. Iron oxide nanoparticles allow the label-free detection of targeted proteins thanks to their high sensitivity to slight variations in the refractive index in the vicinity of the SPR sensor surface. We investigated the very well-known biotin/streptavidin couple in order to study the selectivity of biomolecular binding of our sensor platform. The nonspecific adsorption of proteins was suppressed by using oligo ethylene oxide (EO) chains. A study of the kinetics revealed the remarkably low limit of detection (down to 1.1 nM) which is ascribed to the enhanced accessibility of biotin groups and to the biotin/SA affinity (2.45 × 10 7 M). Indeed, the high radius of curvature of the nanoparticles avoids steric hindrance of the biotin groups and the flexibility of the EO linkers favors their mobility in an aqueous medium. An optimized sensing platform was built by taking advantage of the adequate surface functionalization of iron oxide nanoparticle assemblies supported on a gold thin film.